Large-scale genome sequencing of mycorrhizal fungi provides insights into the early evolution of symbiotic traits - Miyauchi, Shingo; Kiss, Enikő; Kuo, Alan; Drula, Elodie; Kohler, Annegret; Sánchez-García, Marisol; Morin, Emmanuelle; Andreopoulos, Bill; Barry, Kerrie W; Bonito, Gregory; Buée, Marc; Carver, Akiko; et al. (Nature communications, 2020)
Mycorrhizal fungi are mutualists that play crucial roles in nutrient acquisition in terrestrial ecosystems. Mycorrhizal symbioses arose repeatedly across multiple lineages of Mucoromycotina, Ascomycota, and Basidiomycota. Considerable variation exists in the capacity of mycorrhizal fungi to acquire carbon from soil organic matter. Here, we present a combined analysis of 135 fungal genomes from 73 saprotrophic, endophytic and pathogenic species, and 62 mycorrhizal species, including 29 new mycorrhizal genomes. This study samples ecologically dominant fungal guilds for which there were previously no symbiotic genomes available, including ectomycorrhizal Russulales, Thelephorales and Cantharellales. Our analyses show that transitions from saprotrophy to symbiosis involve (1) widespread losses of degrading enzymes acting on lignin and cellulose, (2) co-option of genes present in saprotrophic ancestors to fulfill new symbiotic functions, (3) diversification of novel, lineage-specific symbiosis-induced genes, (4) proliferation of transposable elements and (5) divergent genetic innovations underlying the convergent origins of the ectomycorrhizal guild.
Keywords: Fungal Proteins; houby; Symbiosis; Genome, Fungal; Evolution, Molecular; molekulární evoluce; genom fungální; fyziologie rostlin; rostliny; mykorhiza; Phylogeny; Fungi; Mycorrhizae; fungální proteiny; Plant Physiological Phenomena; Plants; ekosystém; Ecosystem; symbióza; fylogeneze